Overview of the radiographers’ practice in 65 healthcare centers using digital mammography systems in Portugal - Reis, Cláudia Sá dos (2021)
Purpose: To assess current practices in digital mammography (DM) in Portuguese healthcare providers using digital systems. To investigate compliance with European standards regarding mean glandular dose and quality control practice and to identify optimisation needs. Methods: Two questionnaires, targeted at breast radiographers and chief radiographers, were designed and applied in 65 imaging departments offering DM. Questions fielded were focused on the staff profile and technical/clinical practice. Results: Prior to starting their activity in DM, 70% (82 out of 118) of the respondents received training in DM. The practice in 29 out of 59 providers was established by the manufacturers’ recommendations for image acquisition. Variations were observed between radiographers who belong to the same provider namely the selection of exposure parameters such as the target-filter combination and automatic mode. The use of the manual exposure mode was reported for imaging breast implants (44%) and surgical specimens (22%). The main causes of repeat examinations were skin folding (21%) and absence of pectoral muscle (PM) (20%). Conclusions: The study revealed opportunities to optimise radiographers’ practice in DM regarding the selection of exposure parameters. A robust and consistent training programme in DM and established local protocols can help to reduce the variations observed and improve clinical practice. Main Messages: • Radiographers adopted different practices selecting AEC modes and T/F combinations. • Radiographer practice is more consistent using DR than using CR systems. • The main causes for rejecting images were the visibility of skin folding and PM absence. • Radiographers were partly unaware of the dose indicator. • Radiographers’ training needs: QC, interventional procedures and breast dose optimisation.